Detection of Nonadherence to Antihypertensive Treatment by Measurements of Serum Drug Concentrations. Issue 3 (19th July 2021) - Bergland, Ola Undrum; Halvorsen, Lene V.; Søraas, Camilla L.; Hjørnholm, Ulla; Kjær, Vibeke N.; Rognstad, Stine; Brobak, Karl Marius; Aune, Arleen; Olsen, Eirik; Fauchald, Ylva M.; Heimark, Sondre; Thorstensen, Christian W.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Nonadherence to drugs is a challenge in hypertension treatment. We aimed to assess the prevalence of nonadherence by serum drug concentrations compared with 2 indirect methods and relate to the prescribed drug regimens in a nationwide multicenter study. Five hundred fifty patients with hypertension using ≥2 antihypertensive agents participated. We measured concentrations of 23 antihypertensive drugs using ultra high performance liquid chromatography tandem mass-spectrometry and compared with patients' self-reports and investigators' assessment based on structured interview. We identified 40 nonadherent patients (7.3%) using serum drug concentrations. They had higher office diastolic blood pressure (90 versus 83 mm Hg, P <0.01) and daytime diastolic blood pressure (85 versus 80 mm Hg, P <0.01) though systolic blood pressures did not differ significantly. They had more prescribed daily antihypertensive pills (2.5 versus 2.1 pills, P <0.01) and total daily pills (5.5 versus 4.4 pills, P =0.03). Prescription of fixed-dose combination pills were lower among the nonadherent patients identified by serum concentrations (45.0 versus 67.1%, P <0.01). Fifty-three patients self-reported nonadherence, while the investigators suspected 69 nonadherent patients. These groups showed no or few differences in drug regimens, respectively. In summary, we detected 7.3% prevalence of nonadherence by serum drug measurements in patients using ≥2 antihypertensive agents in a nationwide study; they had higher office and ambulatory diastolic blood pressures, higher number of prescribed daily pills, more daily antihypertensive pills, and less frequent prescriptions of fixed-dose combination pills. Indirect methods showed poor overlap with serum drugs concentrations and no or minimal medication differences. Thus, serum measurements of drugs were useful in detection and characterization of nonadherence to antihypertensive treatment. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03209154.